The Implementation of STAD learning model to improve students' learning outcomes - Sirait, Rolina Wati; Sirait, Silvia Hanna Kusuma; Jeni, Jeni (Journal of Research in Instructional, 2024)
The aim of the research was to decide the implementation of the Student Teams Achievement Division (STAD) learning model on the learning outcomes of students in class VII-A at State Junior High School 10 Manokwari. This was a classroom action research that used 16 students from class VII-A as subjects. This research consists of 2 cycles. Each cycle has four stages: Planning, Action Implementation, Observation and Reflection. The results showed that in cycle 1 the average percentage of student learning outcomes reached 63,75, in cycle 1 only 7 students obtained the criteria for completion with a percentage of 43,75% and 9 students who obtained the criteria for incomplete with a percentage of 56,25%. While in cycle 2 the average student learning outcomes have reached 79,37, in cycle 2 who obtained the complete criteria were 15 students with a percentage of 93,75% and only 1 student who obtained the incomplete criteria with a percentage of 6,25%. The research  conclude that student learning outcomes can be improved by implementing the STAD learning model.